Effects of an educational intervention on frailty status, physical function, physical activity, sleep patterns, and nutritional status of older adults with frailty or pre-frailty: the FRAGSALUD study - Casals, Cristina; Ávila-Cabeza-de-Vaca, Laura; González-Mariscal, Andrea; Marín-Galindo, Alberto; Costilla, Manuel; Ponce-Gonzalez, Jesus G.; Vázquez-Sánchez, María Ángeles; Corral-Pérez, Juan (Frontiers in Public Health, 2023)
Introduction The prevalence of frailty is increasing worldwide, emphasizing the importance of prioritizing healthy ageing. To address this, cost-effective and minimally supervised interventions are being sought. This study aimed to assess the impact of an educational program on frailty status, physical function, physical activity, sleep patterns, and nutritional status in community-dwelling older adults with at least 1 Fried’s frailty criteria. Methods A 6-month multicentre randomized controlled trial was conducted from March 2022 to February 2023 in 14 health centres located in Cadiz and Malaga, Spain. The educational intervention consisted of 4 group sessions and 6 follow-up phone calls spread over 6 months. The program focused on educating participants about frailty and its impact on health, providing guidelines for physical activity, healthy dietary habits, cognitive training, psychological well-being and social activities. A total of 163 participants, divided into control (n = 80) and educational groups (n = 83) were assessed before and after the intervention. Results The results showed a significant group-time interaction in the physical function evaluated with a large effect on Short Physical Performance Battery score (η2p = 0.179, −0.1 [−1.2–1.0] points for control group vs. 1.0 [0.0–3.0] points for educational group, p < 0.001), and an effect on the 4-meter gait test ((η2p = 0.122, 0.5 [0.1–0.0] s for control group vs. –0.4 [−0.5– −0.3] s for educational group, p < 0.001), and the 5-repetition sit-to-stand test (η2p = 0.136, 1.0 [0.0–1.2] s for control group vs. −4.3 [−7.0– −2.3] for educational group, p < 0.001). Additionally, the use of accelerometers to assess physical activity, inactivity, and sleep patterns revealed a significant small effect in the number of awakenings at night ((η2p = 0.040, 1.1 [−0.5–3.4] awakenings for control group vs. 0.0 [−2.2–0.0] awakenings for educational group, p = 0.009). The findings also highlighted a significant medium effect regarding malnutrition risk, which was assessed using the Mini-Nutritional Assessment score (η2p = 0.088, −0.7 [−2.3–1.5] points for control group vs. 1.5 [−0.5–3.0] points for educational group, p < 0.001). Discussion Thus, the 6-month educational program effectively improved physical function, sleep patterns, and nutritional status compared to usual healthcare attendance in community-dwelling older adults with frailty or pre-frailty. These findings underscore the potential of minimally supervised interventions in promoting a healthy lifestyle in this vulnerable population.